Violências, conflitos e indisciplinas: discursos em três escolas de educação básica - Marchetti, Rafaela (Universidade Federal de São Carlos, 2020)
This thesis is part of the line of research on Education, Culture and Subjectivity, of the Graduate Program in Education at the Federal University of São Carlos (UFSCAR). It aims to analyze the statements, the singularities, the ruptures and the accumulations in the statements of educators, teachers and employees about conflicts, violence and indiscipline and discuss how disciplinary power relationships occur at school. Discourse analysis based on the studies of Michel Foucault and Jean Jaques Courtine with a focus on discursive formation was used, analyzing the statements and discourses of the speeches involved with the school, in order to understand the power relations in and out their spaces. It´s characterized by a qualitative research, developed in the investigation field, three instruments: documentary research (School Occurrence Books); focus groups (managers, teachers); semi-structured interviews (employees and family).It was found that the fundamental rights of children and young people are discussed at school under the protection of control and discipline. Even with the presence of school principals, the role of school management was not understood. Nothing was explained in the group as a way to solve or mitigate school violence. School violence that which the school institution induces in an institutional, legitimate way was excluded from the statements. In this way, the Municipal Secretary of Education, the municipal government, educators (in general) can´t be responsible for situations of violence in school spaces. The speech reaffirms a situation of impotence of the school in the face of violence, and educators do not feel obliged to develop new perspectives, or pedagogical purposes to establish a more pleasant environment in schools. However, this uncertainty in the solution of the problem directly affects students and their families.
Violences, conflicts and indisciplines: speeches in three basic education schools
Keywords: Violências escolares; Conflitos; Indisciplina; Análise do discurso; Schools violence; Conflicts; Indiscipline; Discourse analys; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO